2015
DOI: 10.1088/2053-1591/2/7/075501
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and material characterization of copper and copper–CNT micropillars

Abstract: In this work, copper micropillars and copper-carbon nanotube (CNT) composite micropillars were fabricated by incorporating an electrodeposition technique with a xurography process. In order to disperse carbon nanotubes in copper-CNT micropillars, various amounts of CNTs were added to the electroplating bath. Surface morphology and phase characterization of copper micropillars and copper-CNT composite micropillars were analyzed by optical microscopy and X-ray diffraction. In addition, the corrosion resistance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The material and corrosion characterization study has been previously reported in detail in an earlier publication by the authors and it is not repeated here for brevity. The interested reader is referred to reference [28] for more detail. Briefly, corrosion resistance of the micropillars was studied using electrochemical impedance spectroscopy (EIS) in a 3.5 wt.…”
Section: Corrosion Characterization Resultsmentioning
confidence: 99%
“…The material and corrosion characterization study has been previously reported in detail in an earlier publication by the authors and it is not repeated here for brevity. The interested reader is referred to reference [28] for more detail. Briefly, corrosion resistance of the micropillars was studied using electrochemical impedance spectroscopy (EIS) in a 3.5 wt.…”
Section: Corrosion Characterization Resultsmentioning
confidence: 99%
“…However, to the author's knowledge, only a single study besides Publication IV has investigated the corrosion performance of embedded carbon nanotubes inside a copper matrix. Ghanbari & Darabi (2015) reported that the corrosion resistance of their CNT-Cu micropillars was increased by six fold when compared with pure Cu micropillars.…”
Section: Corrosion Properties Of Carbon-cu Compositesmentioning
confidence: 99%
“…However, the methods employed to prepare such composites involve using a large amount of toxic and hazardous chemicals and may cause severe pollution . In terms of reliability and non‐toxicity, biosynthesis of nanomaterials is preferred over a physical and chemical approach owing to their reliability and non‐toxicity . Shewanella oneidensis MR‐1, which is widely distributed in the environment, is a bacterium noted for its ability to reduce metal ions .…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29] In terms of reliability and non-toxicity, biosynthesis of nanomaterials is preferred over a physical and chemical approach owing to their reliability and non-toxicity. [30][31][32][33][34][35][36] Shewanella oneidensis MR-1, which is widely distributed in the environment, is a bacterium noted for its ability to reduce metal ions. 37,38 Therefore, it has been used for the biofabrication of noble metals.…”
Section: Introductionmentioning
confidence: 99%